THE IMPORTANCE OF SMART TECHNOLOGIES IN EDUCATION OF THE FUTURE LANGUAGE TEACHERS - Isakova Gulibodom Uktamovna (TADQIQOTLAR.UZ, 2024)
Abstract:As a result of the rapid development of information technologies, which have become an integral part of the modern human environment, smart education is gradually replacing traditional electronic education. The concept of smart education is currently associated with a number of concepts, many of which do not have the same interpretation. Publications on the topic of smart education appeared a few years ago, and they note the main trends in the development of education and create future logical forecasts for further changes in the education system.